Demand-driven innovation policies in the European Union - Camilla Jensen; Itzhak Goldberg (Center for Social and Economic Research (CASE), 2014)
The objective of the PICK-ME (Policy Incentives for Creation of Knowledge - Methods and Evidence) research project is to provide theoretical and empirical perspectives on innovation which give a greater role to the demand-side aspect of innovation. The main question is how can policy make enterprises more willing to innovate? This task is fulfilled by identifying what we consider the central or most salient aspect of a demand-side innovation- driven economy, which is the small and entrepreneurial yet fast growing and innovative firm. We use the term "Gazelle" to signify this type of firm throughout the paper. The main concern of policy-makers should therefore be how to support Gazelle type of firms through various policies. The effectiveness of different policy instruments are considered. For example, venture capitalism is in the paper identified as an important modern institution that renders exactly the type of coordination necessary to bring about an innovation system more orientated towards the demand side. This is because experienced entrepreneurs with superior skills in terms of judging the marketability of new innovations step in as financiers. Other factor market bottlenecks on the skills side must be targeted through education policies that fosters centers of excellence. R&D incentives are also considered as a separate instrument but more a question for future research since there is no evidence available on R&D incentives as a Gazelle type of policy. Spatial policies to foster more innovation have been popular in the past. But we conclude that whereas the literature often finds that new knowledge is developed in communities of physically proximate firms, there is no overshadowing evidence showing that spatial policies in particular had any impact on generating more of the Gazelle type of firms.
Keywords: B52; B53; D78; D83; G24; M13; N94; O3; O43; 330; Innovation; demand-side driven policies; Gazelles; bottlenecks in factor markets; venture capitalism; ontology of knowledge; education systems; clusters